The Civilization of Angkor Wat in the Attitude of Cambodians - Phanthalee, PhraNatthawut (วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย, 2020)
The academic article “The Civilization of Angkor Wat in Cambodian Perspectives” aims to study the civilization land of Angkor Wat in the attitude of Cambodian people or the ancient Khmer empire with full religious and cultural influences from India. Especially beliefs based on Brahmanism or Hinduism Which came into influence before Buddhism for a long time This religion therefore praises the king as a god called “Devarajanism” means that the king is the representative of the deities on the human world, and the means of honoring it is done by building a temple or a temple for it. The mission of all Khmer kings To have to build a stone castle as a temple to the ancestors or to give to himself, therefore the word "castle" here does not mean the palace, the palace which was the residence of the King, but the castle is a religious place that is considered the residence of the gods Human world Architectural styles must be "Religious sites on a layered base" and dug a pool or moat that Khmer called "Barai" surrounded by a stone carving pattern of a serpent, which symbolizes water and fertility. Compare it to Phra Sumen Mountain surrounded by the ocean. Which is a symbol of the solar system according to Hinduism. The stone castle that King Khmer built was the center of the world and the great universe.